THE STRUCTURAL MODIFICATION CAUSES THE ENHANCEMENT OF ANALGESIC ACTIVITY OF 4-(4â€² CHLORO â€“PHENYL)-4- HYDROXY PIPERIDINE - RAFIQ, KIRAN; SAIED SAIFY, ZAFAR; KAUSAR, RANA; RAHIM, NAJIA; NAEEM, SABAHAT (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Objective- The outstandingÂ  position of piperidine analoguesÂ  has proven them an important core in the structures of pharmaceutically active molecules, naturally occurring alkaloids, pharmaceuticals and as synthetic intermediates with interesting biological, physical and pharmacological behaviors. TheÂ  piperidine ring containing compound like pethidine having strong opiod analgesic activity, more potent than codein and controls the pain of smooth muscle spasm. Because of having similarity in structure the present study was aimed to estimate the analgesic activity of synthesized derivatives of 4-(4â€²-Chlorophenyl)-4-hydroxy piperidine. Method- The present study was conducted in animal model, mice by using Pethidine as standard drug. For which the Eddy's hot plate method was adopted and analgesia ( mean increase in latency) Â was observed. Result- The result showed the more prominent response of substituted compound than the parent one 4-(4â€²-Chlorophenyl)-4-hydroxy piperidineâ€ and it was studied that alteration in the molecule structure is accountable forÂ  a better analgesic response. Conclusion- The studies proved the positive pharmacological responsiveness of the combination of 4-(4â€²-Chlorophenyl)-4-hydroxy piperidine with phencyl halides. These synthesized derivatives will establish as potent analgesics. KEY WORDS: Alkaloids Opiod Analgesic Piperidine